Pengembangan Karakter Religius Melalui Praktik Rutin Salat Zuhur Berjamaah Di SMK Muhammadiyah Sumowono Kabupaten Semarang - Wahid Muhammad Zukhruf; Mutohharun Jinan; Mohammad Zakki Azani (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study aims to analyze the development of students’ religious character through the routine practice of congregational zuhur prayer at SMK Muhammadiyah Sumowono, Semarang Regency. This research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that the routine practice of congregational zuhur prayer, implemented in a structured and consistent manner, plays an effective role in shaping students’ religious character, particularly in aspects of discipline, compliance with rules, and religious awareness within the school environment. Daily habituation of worship encourages the internalization of religious values, which is reflected in changes in students’ behavior, such as readiness to perform prayers without teacher instruction and increased responsibility in carrying out religious obligations. The success of religious character formation is supported by synergy among the school, teachers, parents, and the availability of adequate and sustainable worship facilities. Thus, the routine practice of congregational zuhur prayer functions not only as a ritual obligation but also as an instrument of religious character education in Islamic-based vocational high schools. Keywords : Religious Character, Routine Practices, Congregational Zuhur Prayers.